Psychological profiles among high ability undergraduate students. (2nd July 2020) - Rinn, Anne N.; Soles, Kathryn L.; Ferguson, Sarah; Smith, Kendal N.
ABSTRACT: The purpose of this study was to examine the psychological constructs of personality, academic self-concept, and perfectionism using latent profile analysis in order to explore the notion of an undergraduate honors student typology. A sample ( N = 357) of average ability and high ability undergraduates completed measures of personality, academic self-concept, perfectionism, and demographic information. Latent profile analysis resulted in four distinct profiles which were named Insecure and Disorganized Students, Introverted and Driven Students, Laid Back and Socially Focused Students, and Extraverted and Driven Students . Covariate analysis was then conducted to compare the four profiles on covariates of undergraduate grade point average, identification for a gifted program during elementary school, and current undergraduate honors program membership.